Development and validation of the social frailty scale for the older adult in China - Hou, ChaoMing; Gong, XiaoYan; Bai, DingXi; Ji, WenTing; Chen, Huan; Lu, XianYing; Chen, XinYu; Dong, Xiaohui; Gao, Jing (Frontiers in Public Health, 2025)
ObjectivesExisting social frailty instruments are not tailored to the linguistic and cultural characteristics of Chinese-speaking patients; a version addressing this gap will increase clinical understanding of their healthcare experience and may help guide social frailty. To develop a Chinese version of a Social Frailty Scale (CVSFS) for the older adult and to examine the psychometric properties of this instrument.MethodBased on the recommendations of the COSMIN guidelines, the scale development inclued three phases: development of the initial scale, optimisation of scale items, and validation test for scale. The initial CVSFS 1.0 version was developed through literature review, semi-structured interviews, research team discussion, and Delphi method. Then, cross-sectional survey was conducted (n = 265) and scale items were optimized based on the survey results using item analysis and exploratory factor analysis (EFA) to form CVSFS 2.0 version. Lastly, the cross-sectional survey (n = 287) was repeated using CVSFS 2.0 version, and the reliability and validity of the scale's measurement properties were tested.ResultsThe initial scale stage of development formed a 42-item CVSFS 1.0 version. After item analysis and EFA, six items were excluded to form a four-dimension with 36-item CVSFS 2.0 version including individual level, family level, interpersonal level, community and social level. The CVSFS 2.0 version demonstrated good reliability and validity, with a Cronbach's α coefficient of 0.926 and a McDonald's ω estimate of 0.931, split-half reliability of 0.928, and test–retest reliability of 0.978. The I-CVI of the scale was calculated to be 0.889~1.000, and the S-CVI/Ave was 0.930. Confirmatory factor analysis results indicated satisfactory fit indices: χ2/df = 2.17, GFI = 0.813, TLI = 0.932, CFI = 0.937, RMSEA = 0.064.ConclusionsThe CVSFS 2.0 version developed in this study based on a social-ecological framework has high reliability and validity, making it a suitable instrument for evaluating social frailty among the older adult in China.